Pengembangan Modul Pembelajaran Matematika Berbasis Self Regulated Learning Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa UPTD SMP Negeri 1 Mandrehe Barat - Zebua, Syukur Marno Life; Mendrofa, Netti Kariani; Mendrofa, Ratna Natalia; Telaumbanua, Yakin Niat (Universitas PGRI Semarang, 2025)
Students' critical thinking skills in mathematics learning are still low and need to be addressed immediately, particularly at UPTD SMP Negeri 1 Mandrehe Barat. This is influenced by the limited availability of learning materials. As a solution, a Self Regulated Learning (SRL)-based module was developed to encourage independent, reflective, and gradual learning to enhance students' critical thinking skills. This study aims to develop a mathematics learning module based on SRL that is valid, practical, and effective in improving students’ critical thinking skills. This research is a development study using the Plomp model, which consists of three phases: preliminary investigation, prototyping phase, and assessment phase. The instruments used in this research include learning outcome tests, validation questionnaires, and student and teacher response questionnaires. The types of data used in this study are qualitative and quantitative. Qualitative data consist of comments and suggestions from validators regarding the developed module. Quantitative data consist of validation scores, student and teacher responses, and critical thinking test results after using the developed learning material. The results showed that the developed module was highly valid, with validation scores from subject matter expert I at 92%, expert II at 93%, language expert at 82.5%, and design expert at 90%. The module was also considered highly practical, with student response at 90.4% and teacher response at 95%. Furthermore, the module was effective in improving students’ mathematical problem-solving skills, with an average score of 76.34 (moderate category) and classical completeness of 88.46% (very effective category). It can be concluded that the developed SRL-based learning module meets the objectives of the study.